PINK1 phosphorylates transglutaminase 2 and blocks its proteasomal degradation. - Min, B.; Kwon, Y.C.; Choe, K.M.; Chung, K.C. (Journal of Neuroscience Research, 2015)
Parkinson's disease (PD) is characterized by progressive dopaminergic neuronal loss and the formation of abnormal protein aggregates, referred to as Lewy bodies (LBs). PINK1 is a serine/threonine protein kinase that protects cells from stress-induced mitochondrial dysfunction. PINK1 gene mutations cause one form of autosomal recessive early-onset PD. Transglutaminase 2 (TG2) is an intracellular protein cross-linking enzyme that has an important role in LB formation during PD pathogenesis. This study identifies PINK1 as a novel TG2 binding partner and shows that PINK1 stabilizes the half-life of TG2 via inhibition of TG2 ubiquitination and subsequent proteasomal degradation. PINK1 affects TG2 stability in a kinase-dependent manner. In addition, PINK1 directly phosphorylates TG2 in carbonyl cyanide m-chlorophenyl hydrazine-induced mitochondrial damaged states, thereby enhancing TG2 accumulation and intracellular protein cross-linking products. This study further confirms the functional link between upstream PINK1 and downstream TG2 in Drosophila melanogaster. These data suggest that PINK1 positively regulates TG2 activity, which may be closely associated with aggresome formation in neuronal cells. © 2014 Wiley Periodicals, Inc.